Silver chloride supported on Vitamin B1 ‐Organometallic magnetic catalyst: synthesis, density functional theory study and application in A3‐coupling reactions. (31st May 2020) - Esfandiary, Naghmeh; Pazoki, Farzane; Nakisa, Athar; Azizi, Kobra; Radfar, Iman; Heydari, Akbar
Abstract : A highly efficient Fe3 O4 @VitB1 –Ag(I) magnetic catalyst has been obtained using surface modification of Fe3 O4 . To this end, silver chloride was immobilized on Fe3 O4 nanoparticles via vitamin B1 biomolecules. The synthesized biocompatible magnetic catalyst was applied in an A 3 ‐coupling reaction in the presence of aldehyde, amine and phenyl acetylene under solvent‐free conditions and afforded the desired products in excellent yields. Also, interactions between metal and ligand in the Fe3 O4 @VitB1 –Ag(I) were studied using theoretical calculations. Abstract : A highly efficient Fe3 O4 @VitB1 –Ag(I) magnetic catalyst has been obtained using surface modification of Fe3 O4 . To this end, silver chloride was immobilized on Fe3 O4 nanoparticles via vitamin B1 biomolecules. The synthesized biocompatible magnetic catalyst was applied in an A 3 ‐coupling reaction in the presence of aldehyde, amine and phenyl acetylene under solvent‐free conditions and afforded the desired products in excellent yields. Also, interactions between metal and ligand in the Fe3 O4 @VitB1 –Ag(I) were studied using theoretical calculations.